Development of an immunochromatographic strip for rapid detection of H7 subtype avian influenza viruses - Li, Ge (Virol J, 2021)
BACKGROUND: H7N9 avian influenza virus (AIV) including highly and low pathogenic viruses have been detected in China since 2013. H7N9 AIV has a high mortality rate after infection in humans, and most human cases have close contacted with poultry in the live poultry market. Therefore, it is necessary to develop a rapid point-of-care testing (POCT) technique for H7N9 AIV detection. METHODS: The H7N9 AIV was inactivated and purified, and was used as the antigen to immunize BALB/c. Twelve H7-HA specific monoclonal antibodies (McAbs) were produced through the hybridoma technique. The McAb 10A8 was conjugated with colloid gold as detecting antibody; McAb 9B6 was dispensed on the nitrocellulose membran as the capture test line and the Goat-anti mouse IgG antibody was dispensed as control line respectively. The immunochromatographic strip was prepared. RESULTS: The analysis of ELISA and virus neutralization test showed that the obtained McAbs specifically recognized H7 HA. Based on the prepared strip, the detection of H7 AIV was achieved within 10 min. No cross-reaction occurred between H7 AIVs and other tested viruses. The detection limit of the strip for H7 was 2.4 log(10)EID(50)/0.1 mL for chicken swab samples. CONCLUSION: The McAbs were specific for H7 and the immunochromatographic strip developed in this study was convenient, rapid and reliable for the detection of H7 AIV. The strip could provide an effective method for the rapid and early detection of H7 AIV.